The effectiveness of dental health education tools for visually impaired students in Bukit Mertajam - Shahabudin, Saadiah; Hashim, Hasnah; Omar, Maizurah (AIP Publishing, 2016)
Oral health is a vital component of overall health. It is important in adults and children alike, however, it is even more crucial for children with special needs as they have limited ability to perform oral health practices. Disabled children deserve the same opportunity for oral health as normal children. Unfortunately, oral health care is the most unattended health needs of the disabled children. This study aimed to assess the effectiveness of dental health education tools for visually impaired students in two schools in Bukit Mertajam, Penang. The project utilized dental health education tools consisting of an oral health module (printed in braille for the blind and in font 18px for the partially blind), an audio narration of the module were prepared and content-validated by an expert panel. Baseline plaque scores of 38 subjects aged 6-17 years were determined by a trained dental staff nurse. The module was then administered to the subjects facilitated by the teachers. Post intervention plaque scores were recorded again after one month. The pre and post intervention data were analyzed using Wilcoxon Signed Ranks Test with a significant p value set at < 0.05. The results showed that there was a reduction in the overall median plaque score in both partially blind (n = 22) and totally blind (n =16) subjects (2.2 (IQR 0.7) to 1.8 (IQR 0.5) and 2.1 (IQR 0.4) to 2.0 0 (IQR 0.7) respectively). The score difference in the totally blind group was significant (p=0.025). Reductions in plaque scores were also observed in stratified data (based on age); with the partially blind aged 12-17 years showing the greatest reduction. However, the difference was not statistically significant (p=0.067). At younger age, tooth brushing should be supervised by parents as their manual dexterity and cognitive ability is still low. In addition, the younger subjects are less motivated if compared to the older ones. These factors could affect the result of the overall mean OHI-score in this study. In conclusion, the tools appeared to have a positive effect on promoting good oral hygiene among students with visual impairment. We recommend for further studies to be conducted on a bigger sample.